Allogeneic haematopoietic cell transplantation in peripheral T-cell lymphoma: recommendations from the EBMT Practice Harmonisation and Guidelines Committee - Damaj, Gandhi; Bazarbachi, Ali; Berning, Philipp; Cottereau, Anne-Ségolène; Fox, Christopher P; Kyriakou, Charalampia; Cwynarski, Kate; Zinzani, Pier-Luigi; Tournilhac, Olivier; Jurczak, Wojiech; Karsten, Imke E; Wang, Fengrong; et al. (The lancet. Haematology, 2025)
Allogeneic haematopoietic cell transplantation (HCT) is a potentially curative therapy for peripheral T-cell lymphoma; however, to date, there are no standardised and detailed guidelines for its application. To address gaps in clinical practice, the European Society for Blood and Marrow Transplantation (EBMT) Practice Harmonisation and Guidelines Committee convened an international expert meeting in Lille (France) on Sept 30 and Oct 1, 2024. EBMT performed funding acquisition. The chairs invited experts in T-cell lymphoma and HCT, who were organised in two work packages devoted to peripheral T-cell lymphoma and transplantation. A literature search was performed beforehand, and results were presented by subgroups of two or three experts, then discussed collectively in structured discussions, and consensus-building exercises. The recommendations presented in this Review were developed and approved based on current evidence, expert opinion, and clinical experience. These recommendations should help to further establish allogeneic HCT as the standard of care for eligible patients with refractory or relapsed peripheral T-cell lymphoma, leveraging its curative potential through the graft-versus-lymphoma effect.
Online verfügbar 1 July 2025, Version des Artikels 1 July 2025
Gesehen am 04.12.2025